TRENDS IN THE EVOLUTION OF ROMANIA'S PUBLIC REVENUES IN THE PERIOD 2014 – 2023 - POPEANGĂ VASILE NICOLAE (Analele Universităţii Constantin Brâncuşi din Târgu Jiu : Seria Economie)
Our analysis aims to capture the developments recorded by the financial resources mobilized by the state in the reference interval, in order to draw pertinent conclusions regarding the efficiency of the revenue procurement instruments. We will develop the study on two levels, respectively using indicators expressed in nominal terms (current prices) and in real expression (constant prices) in order to eliminate the influences of the inflationary factor and faithfully reproduce the trends followed by the budgetary parameters. The approach demonstrates that, for the time period studied, taxes, fees and contributions have registered a high yield, the dynamics of public revenues being remarkable (+ 143,85% in nominal terms and + 67,10% in real terms) the general conclusion being that the fiscal policy represented a real instrument of the sustainability of the development of the national economy.